2005
DOI: 10.1093/nar/gki863
|View full text |Cite
|
Sign up to set email alerts
|

Real-time expression profiling of microRNA precursors in human cancer cell lines

Abstract: Our previous study described a real-time PCR method to quantify microRNA (miRNA) precursors using SYBR green detection [T. D. Schmittgen, J. Jiang, Q. Liu and L. Yang (2004) Nucleic Acids Res., 32, e43]. The present study adapted the assay to a 384-well format and expanded it to include primers to 222 human miRNA precursors. TaqMan minor groove binder probes were used to discriminate nearly identical members of the let-7 family of miRNA isoforms. The miRNA precursor expression was profiled in 32 human cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
384
2
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(404 citation statements)
references
References 26 publications
13
384
2
5
Order By: Relevance
“…Microarray studies have characterized the modulation of miRNA expression in prostate cancer as compared with normal prostate tissue and identified a number of miRNAs that are up-or downregulated in prostate tumors (Jiang et al, 2005;Mattie et al, 2006;Volinia et al, 2006;Gaur et al, 2007;Porkka et al, 2007;Ozen et al, 2008). In all of these studies, miRNA expression profiles were based on the current databases of miRNAs known at the time (Volinia et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Microarray studies have characterized the modulation of miRNA expression in prostate cancer as compared with normal prostate tissue and identified a number of miRNAs that are up-or downregulated in prostate tumors (Jiang et al, 2005;Mattie et al, 2006;Volinia et al, 2006;Gaur et al, 2007;Porkka et al, 2007;Ozen et al, 2008). In all of these studies, miRNA expression profiles were based on the current databases of miRNAs known at the time (Volinia et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of 222 pre-miRNA was studied by real-time PCR in 32 commonly used cell lines, including 5 breast cancer ones (T47D, SKBR3, MDA361, MCF7 and MDA231) [25]. This study revealed that let-7f-1 is increased by 7-fold in the epithelial-derived breast, lung and colorectal cancer cells.…”
Section: Mirna Are Differentially Expressed In Normal and Tumour Breamentioning
confidence: 95%
“…MicroRNA (miRNA) represent a class of naturally occurring small non-coding RNA molecules (19)(20)(21)(22)(23)(24)(25) nucleotides in length) whose functions are generally unknown, but believed to be important in development. miRNA originate from genes that are transcribed by RNA polymerase II [1].…”
Section: Microrna: Generalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, to further validate the quantity of miRNAs from NGS, one of three methods are typically used, cloned small RNA library technologies [22], northern blot analysis [23], and qPCR [24]. Among these, qPCR is widely used to validate the quantification of gene expression of mRNAs or miRNAs.…”
Section: Resultsmentioning
confidence: 99%